2023
DOI: 10.1101/2023.09.05.556370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From populations to pan-genomes: investigating the role of ecology and genomic architecture in maintaining species boundaries in the porcini mushroom,Boletus edulis

Keaton Tremble,
Etienne Brejon Lamartinière,
Alexander J. Bradshaw
et al.

Abstract: The forces that maintain stable boundaries between closely related groups are poorly characterized in theFungi. In other organisms prezygotic barriers, such as assortative mating, are sufficient to reinforce local adaptation and prevent hybridization, yet assortative mating and other prezygotic barriers are largely absent in most fungi. Postzygotic barriers, such as large structural changes across the genome, can also maintain lineage segregation through hybrid incompatibility. The role of structural variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 124 publications
0
1
0
Order By: Relevance
“…This is to be expected given the high genetic divergence of the lineages, but could lead to issues calling ROHs based on the common reference, as missing sites might result in fewer ROHs being detected with our conservative approach (Thorburn et al, 2023). We therefore mapped the reads from each sample to the lineage-specific reference genomes described by Tremble, Brejon Lamartinière et al (2023): YSU-09856 (N50 = 184 kbp) for the AK lineage, WTU-68809 (N50 = 130 kbp) for the BC lineage, BD-953 (N50 = 329 kbp) for the CO lineage, C-F-109468 (N50 = 170 kbp) for the EU lineage, DUKE-0193972 (N50 = 161 kbp) for the EC lineage, KST39 (N50 = 238 kbp) for the GU lineage, and the pseudochromosomal reference BD747 for the WC lineage. We retained all sites with a depth of coverage ≥9, missing data <10% and mapping quality ≥30, and we removed indels using the following command in Vcftools: '--remove-indels --minDP 10 --minQ 30 --max-missing 0.9'.…”
Section: Genotypingmentioning
confidence: 99%
See 3 more Smart Citations
“…This is to be expected given the high genetic divergence of the lineages, but could lead to issues calling ROHs based on the common reference, as missing sites might result in fewer ROHs being detected with our conservative approach (Thorburn et al, 2023). We therefore mapped the reads from each sample to the lineage-specific reference genomes described by Tremble, Brejon Lamartinière et al (2023): YSU-09856 (N50 = 184 kbp) for the AK lineage, WTU-68809 (N50 = 130 kbp) for the BC lineage, BD-953 (N50 = 329 kbp) for the CO lineage, C-F-109468 (N50 = 170 kbp) for the EU lineage, DUKE-0193972 (N50 = 161 kbp) for the EC lineage, KST39 (N50 = 238 kbp) for the GU lineage, and the pseudochromosomal reference BD747 for the WC lineage. We retained all sites with a depth of coverage ≥9, missing data <10% and mapping quality ≥30, and we removed indels using the following command in Vcftools: '--remove-indels --minDP 10 --minQ 30 --max-missing 0.9'.…”
Section: Genotypingmentioning
confidence: 99%
“…is arguably the most important commercially harvested wild mushroom. It has a broad geographical distribution across Eurasia and North America, where it forms obligate mycorrhizal associations with the dominant northern hemisphere forest tree species (Tremble, Brejon Lamartinière et al, 2023). However, the population dynamics of this species remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown large intraspecific genomic variation in ECM fungi (e.g. Tremble et al, 2023a), raising questions about how natural selection affects ECM fungal populations. What are the signatures of adaptation in ECM fungal genomes?…”
mentioning
confidence: 99%